Treatment of Malignant Bile Duct Obstruction: What the Interventional Radiologist Needs to Know - Camacho, Juan C.; Brody, Lynn A.; Covey, Anne M. (Seminars in Interventional Radiology, 2021)
Management of malignant bile duct obstruction is both a clinically important and technically challenging aspect of caring for patients with advanced malignancy. Bile duct obstruction can be caused by extrinsic compression, intrinsic tumor/stone/debris, or by biliary ischemia, inflammation, and sclerosis. Common indications for biliary intervention include lowering the serum bilirubin level for chemotherapy, ameliorating pruritus, treating cholangitis or bile leak, and providing access for bile duct biopsy or other adjuvant therapies. In some institutions, biliary drainage may also be considered prior to hepatic or pancreatic resection. Prior to undertaking biliary intervention, it is essential to have high-quality cross-sectional imaging to determine the level of obstruction, the presence of filling defects or atrophy, and status of the portal vein. High bile duct obstruction, which we consider to be obstruction above, at, or just below the confluence (Bismuth classifications IV, III, II, and some I), is optimally managed percutaneously rather than endoscopically because interventional radiologists can target specific ducts for drainage and can typically avoid introducing enteric contents into isolated undrained bile ducts. Options for biliary drainage include external or internal/external catheters and stents. In the setting of high obstruction, placement of a catheter or stent above the ampulla, preserving the function of the sphincter of Oddi, may lower the risk of future cholangitis by preventing enteric contamination of the biliary tree. Placement of a primary suprapapillary stent without a catheter, when possible, is the procedure most likely to keep the biliary tree sterile.
Keywords: malignant biliary obstruction; endoscopic stenting; biliary strictures; common bile duct